2017
DOI: 10.5614/j.math.fund.sci.2017.49.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mammary Gland Cancer Development by Propolis and Mangostin in Female Mice Balb/C

Abstract: Abstract. The development of breast cancer involves many processes, including angiogenesis and metastasis. Some factors play a major role in angiogenesis, such as HIF-1α, and in metastasis, such as FAK and Wnt2. The aim of this study was to observe the effect of propolis and mangostin on the development of mammary gland cancer and on the expression of Wnt2 and FAK in Balb/C mice. Mammary gland tumors were induced in Balb/C mice by DMBA. The mice were divided into 5 treatment groups: negative control (K-); posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The combination of propolis and mangostin significantly reduced the expression of Wnt2, FAK, and HIF-1α, when compared to propolis or mangostin alone. 75 Oršolić et al showed that propolis enhanced the tumor-inhibiting effect of cisplatin and improved the survivability of mice with Ehrlich ascites tumor (murine breast carcinoma). They also found that propolis increased the cytotoxic activity of macrophages to tumor cells and sensitivity of tumor cells to hyperthermal intraperitoneal chemotherapy (HIPEC).…”
Section: Combination Effects Of Propolis With Other Anti-cancer Treat...mentioning
confidence: 99%
“…The combination of propolis and mangostin significantly reduced the expression of Wnt2, FAK, and HIF-1α, when compared to propolis or mangostin alone. 75 Oršolić et al showed that propolis enhanced the tumor-inhibiting effect of cisplatin and improved the survivability of mice with Ehrlich ascites tumor (murine breast carcinoma). They also found that propolis increased the cytotoxic activity of macrophages to tumor cells and sensitivity of tumor cells to hyperthermal intraperitoneal chemotherapy (HIPEC).…”
Section: Combination Effects Of Propolis With Other Anti-cancer Treat...mentioning
confidence: 99%